Assessment of the Level of Protein C in Hospitalized Iraqi Patients with COVID-19 and its Correlation with Hematological and Inflammatory Markers - Al-Mamoori, Hind Shaker; Ahmed, Majid Hameed; Al-Nafie, Taha Yaseen Shammar; Al-Attar, Zaid (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: COVID-19 coagulopathy manifests by elevation of certain marker of active coagulation as fibrinogen and this increment associated with increased markers of inflammations. AIM: To measure protein C (PC) level in hospitalized patients with COVID-19 and to find a possible correlation with hematological and inflammatory markers. PATIENTS AND METHODS: Seventy-five hospitalized Iraqi adult patients with COVID-19 were included in a descriptive cross-sectional research. PC, D-dimer, and erythrocyte sedimentation rate (ESR) blood samples were collected, and further information was received from patient’s records. Statistical analysis was conducted using SPSS version 23 and Microsoft Office Excel 2019. RESULTS: Mean age of 75 patients included in the study was 60.13 ± 14.65 years. Sixty-two (62.7%) of patients exhibited neutrophilia, whereas 41 had lymphopenia (54.7%). High ratio of neutrophil/lymphocyte (N/L) was seen in 66 (88.0%), eosinopenia was seen in 46 (61.3%), high lactate dehydrogenase level was seen 68 (90.7%), serum ferritin was high in 66 (88.0%), and high level of C-reactive protein was seen in 68 (90.7%), increased ESR was seen in 69 (92.0%) and high level of D-dimer was seen in 56 (74.7%), while low level of PC was seen in 12 (16.0%) patients. PC had significant negative correlation with prothrombin and partial thromboplastin time but no significant correlation with hematological and inflammatory parameters. CONCLUSION: COVID-19 coagulopathy is common in majority of patients which include significant changes in WBCs counts, inflammatory markers, PC, and D-dimer levels. Such changes may have a great impact on morbidity and mortality and thus need to be monitored throughout treatment and convalescence.